Combined Effects of Cultural-Linguistic Proximity and Naturalization on Political Integration of First-Generation Immigrants - Josep Lobera; Santiago Pérez-Nievas; José Rama (Migraciones, 2021)
Although the under-participation of ethnic minorities in the electoral field is frequently observed, the nuances of their political engagement remain relatively unexplored by scholars. Particularly, little empirical analysis has attempted to identify the barriers faced by first-generation immigrants to adopt a party preference in their host country. Drawing on a unique survey data with a large sample of first-generation immigrants (N= 2,648) in a new migration country (Spain), this article explores the relevance of different set of factors (cultural proximity vs immigration status) in explaining the acquisition of a party preference among this minority population. We find that cultural proximity (as defined by the country of origin: Latin-American vs the rest) is a strong predictor for the acquisition of a party preference. Additionally, our results suggest that the predictive strength of this factor is reinforced through a naturalization regime that facilitates full political rights to culturally closer immigrants, thus reinforcing their a priori better conditions for political integration. Finally, the results also suggest that permissive (rather than restrictive) naturalization policies might work better to secure the political integration of migrant minorities.